2017
DOI: 10.1021/acs.jpclett.7b01901
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical THz-SERS Observation of Thiol Monolayers on Au(111) and (100) Using Nanoparticle-assisted Gap-Mode Plasmon Excitation

Abstract: Surface-enhanced Raman scattering (SERS) microscopy using nanoparticle-assisted gap-mode plasmon excitation, which enables us to observe an atomically defined planar metal surface, was combined with THz-Raman spectroscopy to observe ultra-low-frequency vibration modes under electrochemical conditions. This combination helps us to gain deeper insights into electrode/electrolyte interfaces via direct observation of extramolecular vibrations including information on intermolecular and substrate/molecule interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 37 publications
4
50
1
Order By: Relevance
“…Vibrational spectroscopy is a most powerful surface analysis technique to discriminate molecular information at interfaces. [10][11][12][13][14] Among them, surface-enhanced Raman spectroscopy (SERS) [15][16][17][18][19][20][21] that exhibits ultrahigh surface sensitivity down to single molecules and no interference from water has been widely employed to in situ investigate electrochemical processes including the benzyl chloride reduction at the Ag rough electrode in acetonitrile. [22][23][24] However, most recent studies have found that the plasmon-generated hot electrons of Ag nanostructure during Raman measurements could directly induce the cleavage of the C-X bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational spectroscopy is a most powerful surface analysis technique to discriminate molecular information at interfaces. [10][11][12][13][14] Among them, surface-enhanced Raman spectroscopy (SERS) [15][16][17][18][19][20][21] that exhibits ultrahigh surface sensitivity down to single molecules and no interference from water has been widely employed to in situ investigate electrochemical processes including the benzyl chloride reduction at the Ag rough electrode in acetonitrile. [22][23][24] However, most recent studies have found that the plasmon-generated hot electrons of Ag nanostructure during Raman measurements could directly induce the cleavage of the C-X bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, normal Raman Scattering (RS) spectroscopy (plasmonic enhancement absent) using a conventional singlemonochromator has been shown to be applicable even in the low Raman-shi region below 100 cm À1 (3 THz in vibration frequency), owing to technical advances made in manufacturing ultra-narrow band optical notch lters. [27][28][29] In contrast, SERS spectroscopy remains unexploited in this low Raman-shi spectral region because the background continuum dominates in this region, [30][31][32][33][34][35] leading to a difficulty in analysing the VSERS signals. In the research elds of surface science such as catalysis and electrochemistry, surface-selective spectroscopy for such low-energy vibrations is of particular importance, because useful information on weak forces such as intermolecular interactions 36,37 and substrate/molecule interactions can be provided.…”
Section: Introductionmentioning
confidence: 99%
“…In the research elds of surface science such as catalysis and electrochemistry, surface-selective spectroscopy for such low-energy vibrations is of particular importance, because useful information on weak forces such as intermolecular interactions 36,37 and substrate/molecule interactions can be provided. 30,31,38 Low-energy ERS is also a crucial tool in condensed matter physics, giving access to strongly correlated systems and collective modes such as Cooper pairs and charge density waves. 39 Nevertheless, studies on the SERS background have been mostly carried out in the high Raman-shi region.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In contrast, modern Raman microscopes equipped with a single monochromator and a notch filter give high signal intensity. However, such modern Raman microscopes usually are not accessible to the THz region because of the difficulty in elimination of Rayleigh scattering from the excitation laser, [30][31][32] which makes vibrational studies on phonon modes of gold clusters challenging. 15 Herein, we report experimental and theoretical studies on THz Raman spectroscopy of atomically precise gold clusters protected by phosphine ligands.…”
mentioning
confidence: 99%
“…In the traditional approach, THz Raman spectra are collected using a multiple monochromator, which often suffers from low signal intensity and long integration time. In contrast, modern Raman microscopes equipped with a single monochromator and a notch filter give high signal intensity. However, such modern Raman microscopes usually are not accessible to the THz region because of the difficulty in elimination of Rayleigh scattering from the excitation laser, which makes vibrational studies on phonon modes of gold clusters challenging …”
mentioning
confidence: 99%